The right to freedom of religion and jurisdictional conflicts in Malaysia - Mohamed Azam Mohamed Adil; Wan Naim Wan Mansor; Azril Mohd Amin (Penerbit Universiti Kebangsaan Malaysia, 2023)
In Malaysia, the Federal Constitution provides significant legal protections for religious freedom. Article 11 (1) guarantees the right to profess and practice one's religious beliefs freely, except for restrictions on propagation among Muslims under the federal and state laws (Article 11(4)). Furthermore, according to Article 3 (1), Islam holds a special position in the country. The Malaysian legal system consists of the civil laws and the Syariah laws with two court systems, (example, the Syariah courts and the civil courts). While the former serves as an essential institution for Muslims and maintain the Islamic identity of the nation, issues of jurisdiction have become a subject of contention, particularly in interfaith cases. This study explores an overview of Malaysia's Universal Periodic Review (UPR) on religious freedom and analyses jurisdictional conflicts through interviews with the national legal experts. After carefully considering Malaysia's unique historical and socioeconomic context, it is concluded that upholding the Federal Constitution is of utmost important and implementing the UPR recommendations should be separated from it.